A comparison of physiological responses and rating of perceived exertion in two modes of aerobic exercise in men and women over 50 years of age. Issue 4 (1st August 2002) - Grant, S; Corbett, K; Todd, K; Davies, C; Aitchison, T; Mutrie, N; Byrne, J; Henderson, E; Dargie, H J
Abstract : Objectives: To compare the physiological responses and ratings of perceived exertion to aerobic dance and walking sessions completed at a self selected pace. Methods: Six women and six men with a sample mean (SD) age of 68 (7) years completed aerobic dance and walking sessions in random order. A treadmill test was performed by each subject from which peak oxygen uptake (V̇o 2 ) and maximum heart rates (HRmax) were determined. During the aerobic dance and walking sessions, heart rate and V̇o 2 were measured continuously throughout. Rate of perceived exertion (RPE) was measured every three minutes throughout the session. Results: The sample means (SD) for %peak V̇o 2 were 67 (17)% for the aerobic dance sessions and 52 (10)% for the walking sessions, and the %HRmax sample means (SD) were 74 (12)% for the aerobic dance sessions and 60 (8)% for walking sessions. The sample mean (SD) RPE for the aerobic dance sessions was 11 (2), and for the walking sessions it was 10 (2). Conclusions: %peak V̇o 2, %HRmax, and RPE were significantly higher for aerobic dance than for walking. However, both the aerobic dance and walking sessions were of adequate intensity to improve aerobic fitness in most subjects. Further investigation into the relation between RPE and %peak V̇o 2 in a field setting over representative exercise time periods would be useful.